Goal-setting mechanisms in educational management: a psychological perspective on student and teacher behavior - Wang, Yizhuo; Tang, Shuzhu; Meng, Yang (Frontiers in Psychology, 2026)
ObjectiveTo explore the psychological mechanisms and behavioral impacts of goal-setting mechanisms in educational management.MethodsA cross-sectional survey was conducted with 1,247 students and 358 teachers from 15 schools; data were analyzed using structural equation modeling, multilevel regression, and mediation effect testing.ResultsGoal-setting mechanisms positively affected student learning behavior (β = 0.42, p < 0.001) and teacher teaching behavior (β = 0.38, p < 0.001); learning motivation and self-efficacy played a chain mediating role in students (indirect effect=0.21, 95%CI[0.15,0.28]), while professional identity and teaching efficacy mediated in teachers (indirect effect=0.19, 95%CI[0.12,0.26]); organizational support significantly moderated these relationships.ConclusionScientific goal-setting promotes positive teaching and learning behaviors through psychological pathways, providing insights for educational management.